Ruthenium(II)‐Catalyzed CH/NH Carbonylative Cyclization of 2‐Aryl Quinazolinones with Isocyanates as CO Surrogates. (25th January 2021) - Choi, Jin Ho; Do Kim, Hak; Kang, Ju Young; Jeong, Taejoo; Ghosh, Prithwish; Kim, In Su
Abstract : The ruthenium(II)‐catalyzed CH carbonylation of 2‐aryl quinazolinones with isocyanates as carbonyl sources is described. The developed method provides direct access to biologically relevant isoindoloquinazolinone core through CH aminocarbonylation followed by intramolecular annulation. A broad range of substrate scope and functional group tolerance were observed. Gram‐scale reactions and synthetic transformations demonstrate the synthetic potential of this protocol. Abstract : The CH/NH carbonylative cyclization of 2‐aryl quinazolinones using aryl isocyanates as CO sources under ruthenium(II) catalysis is described.